Reframing Antarctica's ice loss: impacts of cryospheric change on local human activity. (26th March 2021) - Provant, Zachary; Elderbrock, Evan; Willingham, Andrea; Carey, Mark; Antonello, Alessandro; Moffat, Carlos; Sutherland, Dave; Shahid, Sakina
Abstract: Physical scientists, social scientists, humanities scholars, and journalists have all framed Antarctica as a place of global importance—as a laboratory for scientific research, as a strategic site for geopolitical agendas, and more recently as a source of melting ice that could catastrophically inundate populations worldwide. Yet, the changing cryosphere impacts society within Antarctica as well, and this article expands the focus of Antarctic ice research to include human activities on and around the continent. It reframes Antarctica as a place with human history and local activities that are being affected by melting ice, even if the consequences are much smaller in scale than the effects of global sea level rise. Specifically focused on tourism and conservation along the west Antarctica Peninsula (wAP), this article demonstrates the impacts of changing glaciers and sea ice on the timing, location, and type of tourism as well as the ability of changing ice to mediate human experiences through conservation agendas. As future ice conditions influence Antarctic tourism and conservation, an attention to issues emerging within the wAP region offers a new perspective on climate change impacts and the management of Antarctic activities in the 21st-century Anthropocene.